JAKARTA INTERNATIONAL STADIUM : NEW DESTINATION FOR JAKARTA TOURISMADIUM : DESTINASI BARU UNTUK PARIWISATA JAKARTA - Gustian Alkahfi Gustian; Ulfi Maranisya; Rizki Nurul Nugraha (Journal of Tourism Destination and Attraction, 2023)
Jakarta is the capital city of a country with a variety of cultural and historical diversity in its development. It also has tourism potential with many widespread tourists in all corners of the city. With an up-and-coming market, the city of Jakarta has become the business center of the tourism industry in Indonesia, so business opportunities in the form of tourist destinations have the potential to develop on the condition that these destinations have added to be able to reach the market and win market the competition. For this reason, this study will explain a new tourism destination in Jakarta, namely the Jakarta International Stadium located in PapangoPapagong Priok District, North Jakarta Administration City, using a qualitative approach with an exploratory analysis approach, discussion, and Literature Study. The results of this study will identify the history of the Jakarta International Stadium, the 4A component of Tourism, and the potential for tourism development.